INTEGRATIVE ARABIC LANGUAGE TEACHING OF INTEGRATED ISLAMIC ELEMENTARY SCHOOLS IN SOLO RAYA - Rio Kurniawan; Sugeng Sugiyono; Tulus Musthofa (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Integrated Islamic Schools, which is very influential in the education system in Indonesia, stand behind this research. This research explored Arabic language teaching at the Integrated Islamic Elementary Schools in Solo Raya with different integrative system backgrounds. It aimed to answer how the language was taught and learned in Integrated Islamic Elementary Schools in Solo Raya and the learning process from Hector Hammerly's perspective. This research was a field research model with a case study approach under the constructivist research paradigm. The results show that the Arabic language is taught depending on the need in Integrated Islamic Elementary Schools in Solo Raya, and it follows the curriculum of each school. The Hector Hammerly perspective in Arabic language teaching applies cognitive, collaborative, natural, and communicative approaches. The teaching strategies were, among others, presentation, L1 usage, visual aids, practices, error correction, technological aids, evaluation (the students’ performance or teacher-and-student quizzes to evaluate daily progress), and CA-OB (cognitive audio-oral bilingual) method.